Analysis of Dengue Hemorrhagic Fever Prevention Behavior Factors Based on the Theory of Planned Behavio - Prabaningrum, Annisa; Fitryasari, Rizki; Wahyudi, Andri Setiya (International Journal of Psychosocial Rehabilitation, 2020)
Dengue fever is a health problem in tropical and sub-tropical countries due to the low participation of the community in independent prevention of dengue fever. It causes a significant increase in morbidity and mortality. The purpose of this study was to analyze the prevention of dengue hemorrhagic fever based on the Theory of Planned Behavior. The research used a descriptive correlation design with a cross-sectional approach. The population was people who were in the area of ​​Krebet Community Health Center, Madiun City, East Java, Indonesia. The sample was 400 households in Ngale village obtained by a simple random sampling technique. The independent variable consisted of age, gender, education level, knowledge, attitude, and media exposure. The dependent variable was the dengue hemorrhagic fever prevention behavior. Data were collected by questionnaires and observation, then analyzed using the Chi-square test and ordinal logistic regression test. The result showed there was a correlation between knowledge (p=0.000), attitude (p=0.00), gender (p=0.000, an education level (p=0.000)and media exposure (p=0.000) with prevention behavior of dengue hemorrhagic fever. There is no correlation between age and prevention behavior of dengue hemorrhagic fever (p=0.105). The dominant factor affecting the prevention behavior of dengue hemorrhagic fever was the level of education (p=0.00). It is recommended that the government needs to strive to increase knowledge. media exposure. and education.